Mechanistic insights into amphoteric reactivity of an iron-bispidine complex - Mukherjee, Gourab; Velmurugan, Gunasekaran; Kerscher, Marion; Kumar Satpathy, Jagnyesh; Sastri, Chivukula V.; Comba, Peter (Chemistry - a European journal, 2024)
The reactivity of FeIII-alkylperoxido complexes has remained a riddle to inorganic chemists owing to their thermal instability and impotency towards organic substrates. These iron-oxygen adducts have been known as sluggish oxidants towards oxidative electrophilic and nucleophilic reactions. Herein, we report the synthesis and spectroscopic characterization of a relatively stable mononuclear high-spin FeIII-alkylperoxido complex supported by an engineered bispidine framework. Against the notion, this FeIII-alkylperoxido complex serves as a rare example of versatile reactivity in both electrophilic and nucleophilic reactions. Detailed mechanistic studies and computational calculations reveal a novel reaction mechanism, where a putative superoxido intermediate orchestrates the amphoteric property of the oxidant. The design of the backbone is pivotal to convey stability and reactivity to alkylperoxido and superoxido intermediates. Contrary to the well-known O−O bond cleavage that generates an FeIV-oxido species, the FeIII-alkylperoxido complex reported here undergoes O−C bond scission to generate a superoxido moiety that is responsible for the amphiphilic reactivity.
Erstmals veröffentlicht: 09 November 2023
Gesehen am 19.01.2024